2020
DOI: 10.1111/1756-185x.13892
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatology patients' attitude regarding Ramadan and fasting

Abstract: Ramadan, the 9th month of the Islamic calendar, is a sacred month for Muslims. 1 Throughout Ramadan, Muslims should avoid all kinds of food, drinks, drugs, smoking and sexual intercourse between dawn and sunset. 1,2 Two main courses are eaten during Ramadan; 1 just before dawn (Suhur) and the other right after sunset (İftar). The time between the two courses may vary between 12 to 18 hours depending on seasonal and regional characteristics. 3 Studies conducted with healthy individuals suggest that Ramadan fast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Pehlivan et al [55] identified rheumatology patients' attitudes toward RF in a descriptive, cross-sectional study involving 374 patients. Using a questionnaire form, It was determined that 56.1% fasted during Ramadan.…”
Section: Skeletal Medicinementioning
confidence: 99%
“…Pehlivan et al [55] identified rheumatology patients' attitudes toward RF in a descriptive, cross-sectional study involving 374 patients. Using a questionnaire form, It was determined that 56.1% fasted during Ramadan.…”
Section: Skeletal Medicinementioning
confidence: 99%